Numerical simulation of CO2-enhanced oil recovery in fractured shale reservoirs using discontinuous and continuous Galerkin finite element methods - Ma, Tianran; Jiang, Lintong; Liu, Yanbao; Guo, Chaobin; Shen, Weijun; Xu, Yongli (Frontiers in Energy Research, 2024)
Enhanced shale oil recovery through CO2 injection presents a promising approach to simultaneously improve shale oil extraction and reduce CO2 emissions. This study focuses on the application of CO2 flooding in fractured shale reservoir using a discrete fracture-matrix model and the discontinuous Galerkin (DG) and continuous Galerkin (CG) finite element method. The accuracy of the DG-CG FEM presented for solving two-phase flow problem is validated by the McWhorter problem. Then, the model is utilized to simulate CO2 flooding in a fractured shale reservoir, enabling an analysis of the effects of reservoir heterogeneity, fracture permeability, CO2 injection volume, and gas injection patterns on production efficiency and cumulative shale oil recovery. The results of the numerical simulation demonstrate that fractures within the reservoir contribute to enhanced efficiency and increased production volume of shale oil. Compared to homogeneous reservoirs, shale oil production in fractured reservoirs is boosted by approximately 48.9%. Higher fracture permeability enhances reservoir permeability and improves the flow characteristics of shale oil, leading to increased gas production. Increasing the fracture permeability by two orders of magnitude results in a 15.8% increase in shale oil production. Additionally, we observe that higher CO2 injection rates significantly enhance the efficiency of the flooding process. Specifically, a fourfold increase in the CO2 injection rate leads to a 31.5% increase in shale oil production. The simulation results indicate that employing a step-by-step reduction in the injection volume, while keeping the total CO2 injection constant, is more effective. However, it’s important to note that combining higher injection rates with a gradual volume reduction strategy increases the pore pressure within the reservoir. This could potentially lead to rock damage near the wellbore, introducing the risk of gas leakage.